Identificación automática de fases de la microestructura de aceros de fase dual a partir del procesamiento digital de imágenes (2020)
In this project, a computer program was created using MATLAB® software that allows the automatic identification of microstructure phases for microscopies of low-carbon dual-phase steels, where micrographs were analyzed for steels in delivery states and after the application of heat treatment, this software will perform the proper identification of the phases present, their volume fraction, grain size, morphology, distribution, spacing between phases and grain boundaries from the digital image processing.